Chigger Mites (Acari: Trombiculidae) Of Turkey - Stekolnikov, Alexandr; Daniel, Milan (Zootaxa, 2012)
Chigger mites of Turkey were studied on the base of three expeditions (in 1969, 1998, and 2009) and revision of all pre-viously published data on this subject. In total, 43 species from 14 genera parasitizing rodents, soricomorphs, and reptilesin Turkey are considered, 37 of which are identified exactly. Eight new species from the Western and Central Taurus Mtsare described: Xinjiangsha lyciaensis sp. nov., Kepkatrombicula ciliciensis sp. nov., K. taurensis sp. nov., Neotrombiculakizlarsivrisiensis sp. nov., N. kolebinovae sp. nov., N. bolkarensis sp. nov., Miyatrombicula attaliaensis sp. nov., andCheladonta deserticola sp. nov. Twelve species were recorded in Turkey for the first time; moreover, some new recordsfrom other countries were reported (four species were for the first time recorded in Russia, and by one species were re-corded in Armenia, Azerbaijan, Israel, Turkmenistan, and Uzbekistan). For seven chigger genera (Xinjiangsha Wen andShao, 1984, Hirsutiella Schluger and Vysotzkaya, 1970, Lacertacarus Schluger and Vasilieva, 1977, Miyatrombicula Sa-sa, Kawashima and Egashira, 1952, Brunehaldia Vercammen-Grandjean, 1960, Cheladonta Lipovsky, Crossley andLoomis, 1955, and Matacarus Vercammen-Grandjean, 1956), the complete lists of species in the world fauna are provid-ed. Four new synonyms and 18 new combinations were established: Xinjiangsha Wen and Shao, 1984 (= AboriginesiaKudryashova, 1993, syn. nov.), Neotrombicula vulgaris (Schluger, 1955) (= Trombicula acomys Radford, 1957, syn.nov.), Brunehaldia brunehaldi (Vercammen-Grandjean, 1956) (= Eushoengastia (Brunehaldia) aegypti Vercammen-Grandjean and Kolebinova, 1966, syn. nov.), Brunehaldia curtinae (Kepka, 1966) (= Eushoengastia (Brunehaldia) lucida(Schluger, 1966), syn. nov.), Xinjiangsha blanci (Vercammen-Grandjean, 1956), comb. nov., X. danieli (Kolebinova,1974), comb. nov., X. feideri (Daniel and Brelih, 1959), comb. nov., X. galla (Kolebinova, 1970), comb. nov., X. iberica(Schluger, 1957), comb. nov., X. imlilica (Brown, 2008), comb. nov., X. ludmilae (Kováčik and Kalúz, 2010), comb. nov.,X. montana (Kudryashova, 1965), comb. nov., X. monticola (Kolebinova, 1974), comb. nov., X. obuchi (Kováčik and Ka-lúz, 2010), comb. nov., X. raissae (Hushcha and Kharadov, 1987), comb. nov., X. talpae (Kolebinova, 1977), comb. nov.,X. tarda (Schluger, 1957), comb. nov., X. theodori (Hushcha, 1986), comb. nov., X. tshatkalica (Hushcha and Kharadov,1985), comb. nov., X. variabilis (Schluger and Vshivkov, 1967), comb. nov., Brunehaldia spalaxia (Radford, 1957),comb. nov., and Matacarus demrei (Kepka, 1962), comb. nov. A key to genera and species of chigger mites from Turkey is provided.